Tagging Time and Space: TEI and the Canadian Stratford Festival Promptbooks. Issue 1 (31st May 2019) - Roberts-Smith, Jennifer; Kaethler, Mark; Malone, Toby; Giffen, Liza; Holmes, Martin; Jenstad, Janelle; Takeda, Joseph
Abstract : This paper presents the first phase in the development of a new, TEI-based protocol for the encoding of promptbooks. Because the principal function of a promptbook is to record spatiotemporal events whose communicative importance supersedes that of the book in which they are recorded, current standards for digital encoding do not always apply. With the stage managerial artifacts of The. John Gray and the Canadian Stratford Festival Archives as case studies, we provide a rationale for exploring additions to the existing TEI guidelines to account for the unique characteristics of promptbooks.